2010
DOI: 10.1002/elps.201000282
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight determination of high molecular mass (glyco)proteins using CGE‐on‐a‐chip, planar SDS‐PAGE and MALDI‐TOF‐MS

Abstract: The molecular weights (MW) of seven (glyco)proteins, of which five were plasma-derived, with MWs higher than 200 kDa were determined with three techniques: CGE-on-a-chip, SDS-PAGE and MALDI-TOF-MS. While the analysis of medium to high MW proteins with SDS-PAGE was an already well-established technique, the usefulness of MALDI-TOF-MS for the exact MW determination of high mass proteins was only partly described in literature so far. CGE-on-a-chip is the newest of all three applied techniques and was so far not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…MALDI‐TOF MS is the most useful technique for measuring the MW of PEG‐conjugated proteins . The MWs of the LPEG‐proteins and BrPEG‐proteins, including the native proteins and PEG derivatives, measured by MALDI‐TOF MS are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…MALDI‐TOF MS is the most useful technique for measuring the MW of PEG‐conjugated proteins . The MWs of the LPEG‐proteins and BrPEG‐proteins, including the native proteins and PEG derivatives, measured by MALDI‐TOF MS are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…All these chips have been tested for CGE separation of proteins. Performance of microchip-based gel electrophoresis has been compared with that of capillary-based gel electrophoresis [41, 56, 57, 9294]. In general, the performances are comparable, while microchip CGE provides faster separations.…”
Section: Methodsmentioning
confidence: 99%
“…h. Comparisons of methods for N-glycan analysis A comparative study of three techniques, MALDI-TOF, SDS-PAGE and CGE-on-a-chip, for measuring the MWs of large glycoproteins has been reported by Müller et al (2010b). It was found that all three techniques were capable of determining the MW of all high MW (glyco)proteins tested.…”
Section: Detection Of Glycosylation Sites and Site Occupancymentioning
confidence: 99%